Clinicopathologic characteristics and pattern of central lymph node metastasis in papillary thyroid cancer located in the isthmus. (21st April 2016) - Lee, Young Chan; Na, Se Young; Chung, Hoon; Kim, Su Il; Eun, Young‐Gyu
Abstract : Objectives/Hypothesis: The aim of this study was to evaluate the clinicopathologic characteristics and pattern of lymph node (LN) metastasis in papillary thyroid cancer (PTC) located in the isthmus. Study Design: Retrospective cohort study. Methods: One hundred ninety consecutive patients with PTC who underwent total thyroidectomy and bilateral central neck dissection were analyzed. Preoperative ultrasonography was reviewed to identify PTC located in the isthmus. Clinicopathologic factors including age, sex, tumor size, extrathyroidal extension (ETE), margin, angiolymphatic invasion, and nodal metastasis were evaluated. Results: Of 190 PTC patients, 14 patients (7.3%) had a tumor located in the isthmus. The PTCs located in the isthmus were more likely to have ETE and central LN involvement. Furthermore, PTCs located in the isthmus had a higher frequency of metastasis to pretracheal and prelaryngeal LNs than those located in the lobes. Conclusion: PTCs located in the isthmus were associated with ETE and more likely to involve the pretracheal and prelaryngeal LNs. Level of Evidence: 4 Laryngoscope, 126:2419–2421, 2016